DESIGN AND DEVELOPMENT OF AN ANDROID-BASED INFORMATION SYSTEM FOR THE INDONESIAN RED CROSS IN PRINGSEWU REGENCY AS A MEDIA FOR MANAGING MEMBER AND VOLUNTEER DATA - Kevin Maruli Tua Sibuea (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The Indonesian Red Cross (PMI) is an independent and neutral organization engaged in humanitarian work. The PMI in Pringsewu Regency faces challenges in managing member, staff, and attendance data, hindering the development of its Youth Red Cross (PMR) and Volunteer Corps (KSR) activities. Furthermore, public access to information about the PMI in Pringsewu Regency remains limited. Based on these challenges, this study aims to design and build an Android-based information system to manage PMI member and volunteer data in Pringsewu Regency. The research method used is the Waterfall method, encompassing the stages of needs analysis, system design, implementation, testing, and maintenance. The system is equipped with features for member management, volunteer attendance, staff information, and public access to information. Black Box testing results indicate that all system functions operate as required. With this information system, PMI member and volunteer data management in Pringsewu Regency becomes more effective, accurate, and integrated, while also facilitating public access to information about the PMI.